Social Control of Business - Furniss, E. S.; Clark, J. M.; Albrecht, G. (Quarterly Journal of Economics, 1926)
Journal Article Social Control of Business Get access E. S. Furniss E. S. Furniss Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 41, Issue 1, November 1926, Pages 167–170, https://doi.org/10.2307/1885558 Published: 01 November 1926